Gambaran Asuhan Keperawatan Pada Pasien Hipertensi Dengan Gangguan Kebutuhan Rasa Nyaman Nyeri - Gede Ngurah (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2020)
Hypertension is a condition where systole pressure is ˃140 mmHg and diastolic pressure˃ 90 mmHg. The general purpose of this scientific paper research is to find out the description of nursing care for hypertensive patients with impaired comfort needs in the Tabanan Rindam Polyclinic. This type of design uses a descriptive case study, where the research was conducted at the Polyclinic, the study was conducted in February 2019. The subject of the case study will use two clients who were treated in the road at the Tabanan Rindam Polyclinic that met the inclusion criteria. Data collection used in this case study is assessment, diagnosis, intervention, implementation, evaluation. The results of this case study, Nursing diagnosis in this case study, more focused on the patient's comfort, namely pain. Nursing intervention this action is carried out for 2 x 15 minutes using deep breathing relaxation techniques which are known to be able to maintain muscle elasticity so that lowering blood pressure decreases pain scale from scaling pain 5 to pain scale 3. Suggestions from researchers are to provide knowledge to hypertensive patients, especially those who experience discomfort (pain) so that they are able to apply deep breathing relaxation techniques both independently and with guidance.